An Almanack - Joseph Whitaker 1820-1895 (UK, 1908)
Warwick Lane Paternoster Row
F.S.A., containing an account of the astronomical and other phenomena ... information respecting the government, finances, population, commerce, and general statistics of the various nations of the world, with an index containing nearly 20,000 references
Subtitle varies slightly . For the Year of our Lord 1908 . containing the usual [an account of the] astronomical and other phenomena, also a large amount of information respecting the government, finances, population, commerce and general statistics of the British Empire throughout the world, with some notice of other countries
Keywords: Social Sciences (3GdYdhe GdGLJeGYjIs; General; Almanacs, English